E17110 promotes reverse cholesterol transport with liver X receptor β agonist activity in vitro - Ni Li; Xiao Wang; Peng Liu; Duo Lu; Wei Jiang; Yanni Xu; Shuyi Si (Elsevier, 2016)
Liver X receptor (LXR) plays an important role in reverse cholesterol transport (RCT), and activation of LXR could reduce atherosclerosis. In the present study we used a cell-based screening method to identify new potential LXRβ agonists. A novel benzofuran-2-carboxylate derivative was identified with LXRβ agonist activity: E17110 showed a significant activation effect on LXRβ with an EC50 value of 0.72 μmol/L. E17110 also increased the expression of ATP-binding cassette transporter A1 (ABCA1) and G1 (ABCG1) in RAW264.7 macrophages. Moreover, E17110 significantly reduced cellular lipid accumulation and promoted cholesterol efflux in RAW264.7 macrophages. Interestingly, we found that the key amino acids in the LXRβ ligand-binding domain had distinct interactions with E17110 as compared to TO901317. These results suggest that E17110 was identified as a novel compound with LXRβ agonist activity in vitro via screening, and could be developed as a potential anti-atherosclerotic lead compound.